Hidden Benefits of Reward: A Field Experiment on Motivation and Monetary Incentives - Ola Kvaløy; Petra Nieken; Anja Schöttner (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
We conducted a field experiment in a controlled work environment to investigate the effect of motivational talk and its interaction with monetary incentives. We find that motivational talk significantly improves performance only when accompanied by performance pay. Moreover, performance pay slightly reduces performance unless it is accompanied by motivational talk. These effects also carry over to the quality of work. Performance pay alone leads to more mistakes. Adding motivational talk makes the difference. In treatments with performance pay, motivational talk increases output by about 20 percent and reduces the ratio of mistakes by more than 40 percent.
urn:nbn:de:bvb:19-epub-17651-5
Keywords: C93; M52; J33; 330; Verbal Motivation; Performance Pay; Field Experiment